Randomised controlled trial to compare the effect of PIOMI (structured) and routine oromotor (unstructured) stimulation in improving readiness for oral feeding in preterm neonates - Singh, Pari; Malshe, Nandini; Kallimath, Aditya; Garegrat, Reema; Verma, Arjun; Nagar, Nandini; Maheshwari, Rajesh; Suryawanshi, Pradeep (Frontiers in Pediatrics, 2023)
Background Oral motor stimulation interventions improve oral feeding readiness and earlier full oral feeding in preterm neonates. However, using a structured method may improve the transition time to full oral feeds and feeding efficiency with respect to weight gain and exclusive breastfeeding when compared to an unstructured intervention. Objective To compare the effect of Premature Infant Oral Motor Intervention (PIOMI) and routine oromotor stimulation (OMS) on oral feeding readiness. Methods Randomised controlled trial conducted in a neonatal intensive care unit between June-December 2022. Preterm neonates, 29+0–33+6 weeks corrected gestational age, were studied. The intervention group received PIOMI and the control group received OMS. Primary outcome: time to oral feeding readiness by Premature Oral Feeding Readiness Assessment Scale (POFRAS) score ≥30. Secondary outcomes: time to full oral feeds, duration of hospitalisation, weight gain, and exclusive breastfeeding rates. Results A total of 84 neonates were included and were randomised 42 each in PIOMI and OMS groups. The mean chronological age and time to oral feeding readiness were lower by 4.6 and 2.7 days, respectively, for PIOMI. The transition time to full oral feeds was 2 days lower for PIOMI and the duration of hospitalisation was 8 days lower. The average weight gain was 4.9 g/kg/day more and the exclusive breastfeeding rates at 1 month and 3 months post-discharge were higher by 24.5% and 27%, respectively, for the PIOMI group. The subgroup analysis of study outcomes based on sex and weight for gestational age showed significant weight gain on oral feeds in neonates receiving PIOMI. Similarly, the subgroup analysis based on gestational age favoured the PIOMI group with significantly earlier transition time and weight gain on oral feeds for the neonates >28 weeks of gestational age. The odds of achieving oral feeding readiness by 30 days [OR 1.558 (0.548–4.426)], full oral feeds by 45 days [OR 1.275 (0.449–3.620)], and exclusive breastfeeding at 1 month [OR 6.364 (1.262–32.079)] and 3 months [3.889 (1.186–12.749)] after discharge were higher with PIOMI. Conclusion PIOMI is a more effective oromotor stimulation method for earlier and improved oral feeding in preterm neonates. Clinical trial registration https://ctri.nic.in/Clinicaltrials/pdf_generate.php?trialid=70054&EncHid=34792.72281&modid=1&compid=19','70054det', identifier, CTRI/2022/06/043048.